Search for new phenomena in final states with large jet multiplicities and missing transverse momentum using √s = 13 TeV proton-proton collisions recorded by ATLAS in Run 2 of the LHC - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (Journal of high energy physics, 2020)
Results of a search for new particles decaying into eight or more jets and moderate missing transverse momentum are presented. The analysis uses 139 fb−1 of proton-proton collision data at s$$ \sqrt{s} $$= 13 TeV collected by the ATLAS experiment at the Large Hadron Collider between 2015 and 2018. The selection rejects events containing isolated electrons or muons, and makes requirements according to the number of b-tagged jets and the scalar sum of masses of large-radius jets. The search extends previous analyses both in using a larger dataset and by employing improved jet and missing transverse momentum reconstruction methods which more cleanly separate signal from background processes. No evidence for physics beyond the Standard Model is found. The results are interpreted in the context of supersymmetry-inspired simplified models, significantly extending the limits on the gluino mass in those models. In particular, limits on the gluino mass are set at 2 TeV when the lightest neutralino is nearly massless in a model assuming a two-step cascade decay via the lightest chargino and second-lightest neutralino.